Effects of Cardiac Hypertrophy, Diabetes, Aging, and Pregnancy on the Cardioprotective Effects of Postconditioning in Male and Female Rats. (6th May 2019) - Babiker, Fawzi; Al-Jarallah, Aishah; Al-Awadi, Mariam
Abstract : Background . Aging, left ventricular hypertrophy (LVH), diabetes mellitus, and pregnancy are well-recognized risk factors that increase the prevalence of cardio-ischemic events and are linked to poor clinical recovery following acute myocardial infarction. The coexistence of these risk factors with ischemic heart disease (IHD) deteriorates disease prognosis and could potentially lead to fatal arrhythmias and heart failure. The objective of this study was to investigate the vulnerability of hearts with aging, LVH, diabetes, and pregnancy to ischemic insult and their response to pacing postconditioning- (PPC-) induced heart protection. Methods . Hearts isolated from aged, spontaneously hypertensive and diabetic male and female rats and hearts from pregnant female rats (n = 8 per group) were subjected to coronary occlusion followed by reperfusion using a modified Langendorff system. Hemodynamics data were computed digitally, and cardiac damage was accessed by measurements of infarct size and cardiac enzyme release. Results . There were no significant differences in the vulnerability of all hearts to ischemic insult compared to their respective controls. PPC improved cardiac hemodynamics and reduced infarct size and cardiac enzyme release in hearts isolated from aged and spontaneously hypertensive female rats and female rats with hypertrophied hearts subjected to PPC (P < 0.001 ). Aged or hypertrophied male hearts were not protected by PPC maneuver. Moreover, the protective effects of PPC were lost in diabetic male and female hearts although retained in hearts from pregnant rats. Conclusions . We demonstrate that aging, LVH, diabetes mellitus, and pregnancy do not affect cardiac vulnerability to ischemic insult. Moreover, PPC mediates cardioprotection in a gender-specific manner in aged and spontaneously hypertensive rats. Diabetes mellitus provokes the protective effects of PPC on both genders equally. Finally, we demonstrate that PPC is a new cardioprotective maneuver in hearts from pregnant female rats.